It’s Not the Flattery, It’s the Relationship: Rethinking LMX and Workplace Deviance through Ingratiation - Sayidina, Nabilla Azzahra; Fitriastuti, Triana (Jurnal Ilmiah Manajemen & Bisnis, 2025)
This study examines the moderating role of ingratiation in the relationship between Leader–Member Exchange (LMX) and workplace deviance. While prior research has consistently demonstrated that high-quality LMX reduces deviant workplace behavior through increased trust and mutual support, limited attention has been given to how impression management tactics, such as ingratiation, may influence this relationship. Drawing on a quantitative approach, the study analyzes data from (395) employees across diverse industries in Indonesia. The results indicate that ingratiation significantly moderates the effect of LMX on workplace deviance. Specifically, the negative association between LMX and deviance becomes stronger when ingratiation is high. This finding challenges the conventional assumption that ingratiation is inherently dysfunctional and suggests instead that, in the context of strong leader–subordinate relationships, its potentially negative effects can be socially regulated. The study contributes to the literature by positioning ingratiation not only as a behavioral risk but also as a contextual trigger that activates LMX's adaptive control function. Practically, the findings underscore the importance of strengthening high-quality workplace relationships while managing political behavior as part of developing a constructive and ethical organizational culture.